CURRENT STATE OF TICK-BORNE BORRELIOSIS (LYME DISEASE) IN CHILDREN - N. N. Zvereva; K. Shakaryan; R. F. Sayfullin; A. L. Rossina; Yu. Rtishchev; Kh. Belyaletdinovа (Детские инфекции (Москва), 2017)
Literature review describes the problem of Tick-borne Borreliosis (Lyme Disease). The review analyzes modern date on etiology, epidemiology,  clinical course, treatment and prognosis of disease in children. The modern capabilities of diagnosis are discussed.